1984
DOI: 10.1021/i200027a001
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic pyrolysis of a coal tar in a fixed-bed reactor

Abstract: The product yields from cracking a bituminous coal tar In a fixed-bed reactor were determined at various temperatures in the presence and absence of some packing materials. Synthetic zeolttes, Linde LZ-Y82, Norton Zeokn 900-H, and Davison 13-X, as well as a natural zeolite, chabarite, showed strong catalytic activity. I n contrast, molecular sieves 5-A and natural erionite having smaller pore diameters were found to be much less active. Clay minerals such as kaolinite, montmoriibnlte, and Kieselguhr exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 3 publications
2
36
0
1
Order By: Relevance
“…The importance of this equation with regard to product yields and composition with the addition of dolomite or calcite was previously confirmed [43,56]. If the yields are taken into account in the current study it seems probable that the left hand side of the equation is favoured by the presence of minerals within the coal matrix.…”
Section: Co2 Yieldsupporting
confidence: 63%
See 3 more Smart Citations
“…The importance of this equation with regard to product yields and composition with the addition of dolomite or calcite was previously confirmed [43,56]. If the yields are taken into account in the current study it seems probable that the left hand side of the equation is favoured by the presence of minerals within the coal matrix.…”
Section: Co2 Yieldsupporting
confidence: 63%
“…In previous studies, this was attributed to assist the decrease in tar yield [5,6]. The effect of kaolinite in tar reduction is attributed to the acidity of the mineral, thus providing protonates for increased pyrolysis conversion [5,6,43]. Kaolinite is however less active than dolomite and calcite in tar reduction [6,44].…”
Section: Tar Yieldmentioning
confidence: 98%
See 2 more Smart Citations
“…It is generally accepted that the strong sites of acidity in the zeolites are the key factor in cracking activity, and the pore size of the zeolites influence the cracking activity too. Wen and Cain (1984) found that a zeolite with a pore size of >0.7 nm is effective for converting coal tar to light products. Their explanation was as follows: although many molecules in coal tar are too large to enter into the pores with diameters of about 0.8 nm, a side group or a part of the large molecule can be partially trapped on the surface of a zeolite and cracked to smaller molecules.…”
Section: Solubilities Of Reaction Mixturesmentioning
confidence: 99%